2021
DOI: 10.4314/wiojms.si2020.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical modelling of coastal upwelling variability and circulation along the Tanzanian and Kenyan coasts

Abstract: Ocean circulation, upwelling phenomena and chlorophyll-a concentrations were investigated within the framework of numerical model simulations with 1/12° nested horizontal grid-size, in the tropical western Indian Ocean, along the coasts of Tanzania and Kenya. Ekman driven upwelling exhibited high levels of spatial and temporal variability in the region, characterized by a more vigorous occurrence/intensification during the Northeast than the Southwest Monsoon season. A similar trend was observed for chlorophyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
2
1
0
Order By: Relevance
“…Long-term trends were stronger during the SWM than during the NEM, with increased wind speeds for Tanga and Zanzibar in the north but a decline in the maximum wind speed for Mtwara in the south and constant maximum wind speeds for Dar es Salaam. A coastal upwelling index (CUI) based on SST output from a coupled biophysical-climatological model by Halo et al (2020) showed a moderate and steady linear increase in upwelling for Tanga over a 23-year period , in line with the regional increase in wind speed observed by Mahongo et al (2012).…”
Section: Productivity and Ecosystem Impactssupporting
confidence: 57%
See 2 more Smart Citations
“…Long-term trends were stronger during the SWM than during the NEM, with increased wind speeds for Tanga and Zanzibar in the north but a decline in the maximum wind speed for Mtwara in the south and constant maximum wind speeds for Dar es Salaam. A coastal upwelling index (CUI) based on SST output from a coupled biophysical-climatological model by Halo et al (2020) showed a moderate and steady linear increase in upwelling for Tanga over a 23-year period , in line with the regional increase in wind speed observed by Mahongo et al (2012).…”
Section: Productivity and Ecosystem Impactssupporting
confidence: 57%
“…This small upwelling cell has been observed in both monsoons (Fig. 11), suggesting it is a regular occurrence (Halo et al, 2020).…”
Section: Mechanismssupporting
confidence: 55%
See 1 more Smart Citation
“…These conditions place resident marine organisms and coastal ecosystems at a high risk of future ocean acidification and deoxygenation (Cornwall et al, 2023;Kroeker et al, 2023). Although the extensive impacts of upwelling events on pH, DO, and temperature dynamics are well-documented globally (Rixen et al, 2012;Schulz et al, 2019;Kroeker et al, 2023), this information is largely unknown in coastal upwelling areas of the Western Indian Ocean (WIO), particularly in the Tanga-Pemba Seascape (T-PS), known to experience upwelling during the northeast monsoon season (Halo et al, 2020;Kyewalyanga et al, 2020). This information is crucial for informing the future of global change biology in the WIO.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this study was twofold. Firstly, to understand high-frequency dynamics in pH, DO, and temperature in the open ocean of the T-PS during the northeast monsoon, when upwelling events are thought to occur (Halo et al, 2020;Kyewalyanga et al, 2020), as well as the 24-hour high-frequency dynamics of these variables in mangrove, seagrass, and coral reef ecosystems within the seascape. Secondly, to understand the susceptibility of mangrove, seagrass, and coral reef ecosystems to lower pH and DO conditions induced by upwelling events and whether some of these ecosystems offer any degree of mitigation under such events.…”
Section: Introductionmentioning
confidence: 99%